Voices Project: Technological Innovations in Social Inclusion of People with Visual Impairment - Cazini,Janaina (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
This article aims to analyze how technological innovations are contributing to inclusion of people with disabilities in society and at work, from the study of social innovations, assistive technology and digital inclusion presented in a case study on the Voices Project. The project, developed in partnership with the Association of Parents and Friends of the Blind and the Federal Technological University of Paraná, in the years 2008/2009, made a computer course for people with visual impairments. The theoretical survey and project data confirmed that social innovations really are essential tools for digital inclusion of people with disabilities contributing thus to their inclusion in the workplace.